Living a successful weight loss after severe obesity - Eli Natvik; Målfrid Råheim; John Roger Andersen; Christian Moltu (International Journal of Qualitative Studies on Health & Well-Being, 2018)
Purpose: Losing weight and keeping it off for the long term is difficult. Weight regain is common. Experiences of successful non-surgical weight loss after severe obesity are largely unexplored. We know little about long-term weight loss processes, and how health care services can be of help to those living them. Methods: Drawing on in-depth interviews of 8 women and 2 men, the aim of this phenomenological study is to describe the experiences of adults who have been severely obese, who have lost weight and maintained weight loss for the long term (>5 years). Results: Findings show that after severe obesity, sustained weight loss has no endpoint, yet is always easy to end. Keeping weight off means committing to oneself, continuing profound changes and cultivating sensitivity towards oneself and others. A phenomenological understanding of sustained weight loss can inform professionals who deal with health issues and challenges occurring in the life of people leaving severe obesity.